Elevating the Prestige of the Teaching Profession Through Educational Reform and Sustainable Development Goals (SDGs) Integration - Mukhlisa Dustnazar Omonova; Malyudaxon Musurmonova; Gulasal Tadjalievna Khojikarimova; Oxistaxon Qosimjonovna Dehqonova; Gulnigorbonu Barkhayotjon Mamatkulo; Bobomurot Saitxonov Pulatovich; Doniyorova Iroda Baxtiyor; Sanam Fakhriddinovna Abduvositova (Bumi Publikasi Nusantara, 2025)
This study aims to explore strategies for enhancing the prestige of the teaching profession by linking educational reform with Sustainable Development Goals (SDGs), particularly those related to quality education and decent work. Using a three-phase experimental approach, the research engaged teachers in professional development within educational clusters. Findings showed significant improvements in teacher prestige and motivation, supported by data from pre- and post-tests. These gains were attributed to targeted interventions such as technological literacy, community engagement, and continuous capacity-building, because they addressed both systemic and personal dimensions of the teaching profession. The impact of this study lies in providing a model that supports professionalization in education while contributing to the realization of SDG 4 and SDG 8.